The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.26773/smj.190212
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference, Nutritional Supplements and Drug use in Sport to Enhancing Performance: an Italian Revision over the Last Decade

Abstract: In last years, there has been a multitude of studies on doping, such as in recreational and in amateur sport. The extent of this phenomenon was clarified for special populations (like e.g. bodybuilders) and for special substances (mostly for anabolic steroids). Doping is present in sportsmen and women; the reasons why may be many and various. The aim of this study is to discover the gender disparity of drugs addiction as doping practice and breakdown by sport bodies and gender. The data show the anti-doping te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
3
9
0
1
Order By: Relevance
“…While competitive athletes have planned surveillance of their activities, amateur athletes have different sources of knowledge about the characteristics of PA. This might determine the adoption of habits not useful to reach adequate level of PA (immoderate use of food supplements, drug abuse to improve performance, overtraining programs increasing the risk of injuries) [33,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…While competitive athletes have planned surveillance of their activities, amateur athletes have different sources of knowledge about the characteristics of PA. This might determine the adoption of habits not useful to reach adequate level of PA (immoderate use of food supplements, drug abuse to improve performance, overtraining programs increasing the risk of injuries) [33,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the published literature reported that the consumptions of NS depends on several factor: the type of sport, the sex of the athletes and the level of competition (Pesce et al 2004;Mazzeo, F., Santamaria, S., & Montesano, P.,2019). For example, in the study of Burke &Read 1993 andBrill &Keane 1994, all the analysed weightlifters or bodybuilders intake NS (Burke et al 1994;Brill et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The use of nutritional supplements should be carefully taken into consideration, due to their metabolic effects; for example, the abuse of anabolic-androgenic steroids shows an increased risk of upper body tendon rupture [57]. Particularly, this aspect is even more important for professional athletes, for whom some substances could violate the doping regulamentation and be considered illegal [58].…”
Section: Nutritionmentioning
confidence: 99%